An Introduction to Modelling of Power System Components - Krishna, S. (SpringerBriefs in Electrical and Computer Engineering, 2014)
TheÂ brief provides a quick introduction to the dynamic modelling of power system components.Â It gives a rigorous derivation of the model of different components of the power system such as synchronous generator, transformer, transmission line, FACTS, DC transmission system, excitation system and speed governor. Models of load and prime movers are also discussed. The brief can be used as a reference for researchers working in the areas of power system dynamics, stability analysis and design of stability controllers. It can also serve as a text for a short course on power system modelling, or as a supplement for a senior undergraduate/graduate course on power system stability.